MODELING OF REMOTE FIELD EDDY CURRENT TRANSIENT PHENOMENA - Raugi, M. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
An integral formulation is presented and used for the analysis of the Remote Field Eddy Current (RFEC) transient phenomena. The model presented allows simple and accurate modeling of RFEC systems in the presence of axisymmetric defects. The method has been validated first by comparison of the computed results with results obtained with an analytical model. Then the method was used to show that the Remote Field effect is mainly due to a direct induction effect rather than propagation effects. The Remote Field effect phenomena are usually analysed using a steady state domain. However, the results obtained here have shown that detection of defects is not due to a steady state phenomenon, but depends mainly on the transient signal. [Vol. 11, No. 2 (1996), pp 72- 75]